Effect of Work Motivation, Training, and Work Discipline on the Performance of State Civil Apparatus in the Municipal Police Unit and Fire Department of Merauke Regency - Irianto Sabar Gattang (Britain International for Academic Research (BIAR) Publisher, 2022)
The objective of this study was to test and analyze the effect of work motivation, training, and work discipline on the performance of state civil apparatus in the Municipal Police Unit and Fire Department of Merauke Regency. This study used an associative quantitative approach by using a saturation sampling technique, obtaining a total sample of 106 people. The variables were measured using Likert scale, while the data were analyzed using SPSS. The results of the analysis showed that work motivation had no effect on the performance of state civil apparatus. Meanwhile, training and work discipline were proven to have a positive and significant effect on the performance of state civil apparatus. The results of the statistical test showed that the variables of work motivation, training, and work discipline can explain the performance of state civil apparatus by 67.8%.